Analysis of Employee Work Discipline in The Office Sukasari Village, Sumedang - Deni Sahya; Solihin Royani; Wulan Ariani Damayanti (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
The focus of this study is to analyze how the implementation of Employee Work Discipline in Sukasari Sumedang Village Office. The purpose of this research is for work discipline and how to apply work discipline as well as obstacles and solutions. The design of this research using qualitative method that is descriptive by conducting direct observation, conducting interviews, collecting data in the form of documents. Researchers use qualitative methods with case study approach. Creswell in Sugiyono (2020:6) case study is one type of qualitative research, where researchers conduct an in-depth exploration of programs, events, processes, activities, against one or more people. According to Bejo Siswanto in Lijan Poltak Sinambela (2019:356) are indicators that affect work discipline including attendance frequency, level of vigilance, adherence to work standards, adherence to work rules and work ethic. The target of the informant that the researcher chose was the Village Head, Secretary, and Sukasari Village Employee. Based on the results of the interview, it was concluded that the work discipline at sukasari sumedang village office has been running optimally in accordance with the regulations applied oraganisasi. In addition, the implementation of employee work discipline is based on the basis of consideration in the form of prohibitions and obligations applicable to employees.